2007
DOI: 10.2116/analscix.23.x67
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Novel Complex of 1,3-Bis(2-methoxybenzene)triazene with Mercury(II)

Abstract: Recently, the 1,3-bis(2-methoxybenzene)triazene ligand was synthesized and its crystal structure reported.1 Structural and solution studies of a novel tetranuclear silver(I) cluster of this ligand ([AgL]4·THF) have also been reported. 2 In this paper, we report on the synthesis of the [ClHgL] complex of this ligand and discuss the basis of the experimental results, especially the X-ray diffraction data, concerning the crystal and molecular structure of the compound (Fig. 1). The title complex was synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…For 2a and 3a the size of the η 1 ‐bonded triazenide ligands enforces the formation of strictly monomeric compounds in which the metal atoms show a linear coordination by the Mph‐bonded nitrogen atom N3 and one halogen atom, respectively. The Hg–N3 distances of 2.090(3) Å ( 2a ) and 2.153(12) Å ( 3a ) are similar or slightly longer than the corresponding distances in three structurally characterized homoleptic mercury triazenides [2.060(5)–2.077(4) Å] 11, a triazenidomercury nitrate [2.101(8) Å] 13 and a donor‐stabilized triazenidomercury chloride [2.075(4) Å] 15. Much longer distances are observed to the Dmp‐bonded nitrogen atom N1 and the central nitrogen atom N2 with values > 2.63 Å and > 2.85 Å, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…For 2a and 3a the size of the η 1 ‐bonded triazenide ligands enforces the formation of strictly monomeric compounds in which the metal atoms show a linear coordination by the Mph‐bonded nitrogen atom N3 and one halogen atom, respectively. The Hg–N3 distances of 2.090(3) Å ( 2a ) and 2.153(12) Å ( 3a ) are similar or slightly longer than the corresponding distances in three structurally characterized homoleptic mercury triazenides [2.060(5)–2.077(4) Å] 11, a triazenidomercury nitrate [2.101(8) Å] 13 and a donor‐stabilized triazenidomercury chloride [2.075(4) Å] 15. Much longer distances are observed to the Dmp‐bonded nitrogen atom N1 and the central nitrogen atom N2 with values > 2.63 Å and > 2.85 Å, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Structurally characterized mercury triazenides have been limited so far to several unsolvated 11 and solvated bis(diaryltriazenido) species 12, a mercury nitrate 13 and two heterobimetallic complexes 14. Very recently, the structural characterization of a donor‐stabilized mercury chloride was reported 15. For 2a and 3a the size of the η 1 ‐bonded triazenide ligands enforces the formation of strictly monomeric compounds in which the metal atoms show a linear coordination by the Mph‐bonded nitrogen atom N3 and one halogen atom, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the synthesis of the ligands 1,3‐bis(2‐methoxyphenyl)]triazene,6 [1,3‐bis(2‐ethoxyphenyl)]triazene,7 and [1,3‐bis(2‐cyanophenyl)]triazene8. Additionally, we have published Hg II complexes with [1,3‐bis(2‐methoxyphenyl)]triazene by using HgCl 2 9 and HgBr 2 10 as starting materials. In addition, Ag I and Cd II complexes with this ligand are known 11,12.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, a complex containing the title ligand and Hg(II) cation was synthesized and its crystal structure reported. 2 In this complex one Cl atom on HgCl2 salt was replaced by L and a tetrahedral geometry was formed. In addition, a complex containing four molecules of L and four Ag(I) atoms was synthesized and its crystal structure and solution studies reported.…”
mentioning
confidence: 99%